공동주택 전용 갱폼 인양 자동화 기술 개발에 관한 연구 - 양상훈; 조재용; 조지원; 이정호; 김영석; Yang, Sang-Hoon; Cho, Jae-Yong; Cho, Ji-Won; Lee, Jeong-Ho; Kim, Young-Suk (한국건설관리학회 논문집, 13(1), 2012)
Gangform compared with conventional wood and steel form is systemized form which has a capability to install and dismantle form at a time without repeating to assembly and disassembly small members. Gangform compared with ACS has some problems such as 1) Tower Crane load increase, 2) increase in safety incidence during climbing Gangform, 3) decrease in detachment operation productivity, 4) stop work due to climate impacts, and 5) decrease in labor cost, productivity, quality. A conceptual design model of automated Gangform climbing system is suggested for apartment housing construction to show its technical/economic feasibility and workers' safety while increasing operation productivity and concrete quality. 갱폼은 기존 목재 및 철재 거푸집과 비교하여 매 사용 시 작은 부재의 조립/해체를 반복하지 않고 대형화, 단순화를 통해 한 번에 설치하고 해체할 수 있는 시스템화 된 거푸집이다. 그러나 ACS(Auto Climbing System)와 같은 첨단 거푸집에 비해 경제성을 제외한 다른 측면(생산성, 안전성, 품질 등)에 있어서는 1) 타워크레인 양중부하 증가, 2) 갱폼 인양 중 안전사고 증가, 3) 갱폼 박리 작업 생산성 저하, 4) 기후 영향으로 인한 작업 중지, 5) 생산성, 노무비, 품질 저하 등의 문제점을 지니고 있는 것으로 조사되었다. 따라서 본 연구에서는 타워크레인의 부하를 감소시킴과 동시에 인양 속도를 향상시킴으로써, 작업 생산성 향상 및 노무자 안전성 확보, 콘크리트 구조체의 품질 등을 향상시켜 공동주택 건설 현장에서 범용적으로 사용가능한 공동주택 전용 갱폼 인양 자동화 장비의 개념 모델을 제시하고자 한다. 이를 위해 본 연구에서는 기존 문헌 분석 및 건설 현장관리자와의 설문조사를 수행하여 공동주택 전용 갱폼 인양 자동화 기술 개발 시 요구되는 고려요소 도출 및 효용성 분석 등을 통해 '공동주택 전용 갱폼 인양 자동화 장비의 개념 모델'을 제시하였다.